Determinants of HIV/AIDS knowledge among early adolescents in junior high school: A cross-sectional study - Ni Putu Citra Laksmi; Titin Novayanti Dey; Putu Eva Yuni Dyantari; Luh Citrarasmi Dara Mestika; Sumiati Sumiati; Luh Yenny Armayanti (Journal of Midwifery and Nursing, 2026)
HIV/AIDS infection remains a crucial global public health issue, with a significant increase in cases every year in Indoneia, and adolescents occupy vulnerable positions. Limited knowledge related and the burden of social stigma hinders the effectiveness of intervention programs. This study aims to find out in depth the level of knowledge of junior high school adolescents about HIV/AIDS. This descriptive quantitative research uses a cross-sectional design with purposive sampling technique. The sample consisted of 52 grade IX students of SMP 1 Sawan. The results showed that the majority of respondents were 15 years old (55.8%) and female (67.3%). The level of adolescent knowledge about HIV/AIDS is mostly in the moderate category (65.4%), with the lowest score being 60, the highest score being 83.3, the mean being 68.3, and the median being 70. This indicates that there is still a need to provide information related to HIV/AIDS. The topic of HIV transmission has the highest proportion of wrong answers, followed by the signs and symptoms of HIV/AIDS. It is recommended that schools, parents, and the government work together in efforts to improve comprehensive and sustainable education, including strengthening Pelayanan Kesehatan Peduli Remaja (PKPR).